PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR PADA SISWA KELAS XI IPS SMA NEGERI 1 SELAYAR - WARSIDAYANA; RAMHATULLAH; INANNA; MUHAMMAD RAKIB; MUHAMMAD HASAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The aim of this study is to the determine the impact of the application of discovery learning models on the economic learning outcomes of class XI IPS at SMA Negeri 1 Selayar. This researches is a descriptive study using quantitative methods. The data was collected through observation, questionnaires and documentation. The population in this study consisted of all class XI IPS students with a sample of 81 students selected from each class by simple random sampling. The results of the study were analyzed using a simple linear regression analysis. Based on the results of the research and data analysis, it was concluded that the application of the discovery learning model has an impaction the economic learning outcomes of class XI IPS at SMA Negeri 1 Selayar.